DESIGN OF INDOOR AIR QUALITY MONITORING SYSTEM FOR AIR VENTILATION SYSTEM EFFECTIVENESS IN ENGINEERING PHYSICSâ MULTIMEDIA ROOM OF LABTEK VI INSTITUTE OF TECHNOLOGY BANDUNG - Putri Kamilah, Salsabila
Human spent almost 90% of their time indoors, is not a short amount of time. Even with the long duration of human intensity in the room, the quality of the indoor environment is need to be ensured about its health, comfort, and safety. One of the factors that determines the quality of the indoor environment is air. Air that is invisible and cannot be felt, as well as pollutants that cannot be detected directly by the five senses such as carbon dioxide, can be harmful or dangerous to health and detrimental if not noticed. As a room occupant, it is necessary to find out whether the indoor air quality (IAQ) is good. Control of air flow patterns or poor circulation is the main reason for the low quality of room air. Air circulation involves various factors, ranging from air flow (air velocity, rate of air change), to room climatic conditions (temperature, relative humidity, pollutant concentration, especially carbon dioxide). Pollutant detection sensors are widely used to determine room air quality as in previous studies and this study. This study will use the XY-MD02 (SHT20) sensor to obtain information on the temperature and relative humidity values of the room and the SenseAir S8 sensor to obtain information on the room’s carbon dioxide concentration. Supported by rapid technological advances, the monitoring system that is being designed in this study can be modified so that data on room conditions can be obtainded directly and real time. It can also be monitored remotely by utilizing Internet of Things (IoT) technology. Monitoring the condition of indoor air quality using IoT technology is also one of the efforts to convert conventional buildings into smart buildings that are environmentally friendly nowadays. Further action to meet the ideal indoor air quality conditions is needed after knowing the indoor air quality conditions. One strategy to control indoor air quality is through ventilation techniques. The room air ventilation system is designed so that the room gets fresh air continuously and air exchange can occur in the room. The output from monitoring the conditions of the air quality of the room before, is used to determine how effective the room ventilation system is, where in this study two experiments were carried out for exhaust as a mechanical ventilation system that was conditioned open and closed, and the window of the room as a natural ventilation system that was conditioned open and closed. Additional variables in the form of the number of occupants of the room were also tested from no occupants to full according to the limit on the number of occupants of the room. The results of monitoring the independent variables of exhaust openings, windows, and the number of occupants of the room were compared to determine the best conditions when the carbon dioxide concentration in the room was below the threshold and the room was well circulated. The best room conditions are then used as the basis for a Computational Fluid Dunamics (CFD) simulation which will confirm the air distribution of the room.